Cognitive Dysfunction following Cerebellar Stroke: Insights Gained from Neuropsychological and Neuroimaging Research - Qi Liu; Chang Liu; Yu Chen; Yumei Zhang (Neural Plasticity)
Although the cerebellum has been consistently noted in the process of cognition, the pathophysiology of this link is still under exploration. Cerebellar stroke, in which the lesions are focal and limited, provides an appropriate clinical model disease for studying the role of the cerebellum in the cognitive process. This review article targeting the cerebellar stroke population (1) describes a cognitive impairment profile, (2) identifies the cerebellar structural alterations linked to cognition, and (3) reveals possible mechanisms of cerebellar cognition using functional neuroimaging. The data indicates the disruption of the cerebro-cerebellar loop in cerebellar stroke and its contribution to cognitive dysfunctions. And the characteristic of cognitive deficits are mild, span a broad spectrum, dominated by executive impairment. The consideration of these findings could contribute to deeper and more sophisticated insights into the cognitive function of the cerebellum and might provide a novel approach to cognitive rehabilitation. The goal of this review is to spread awareness of cognitive impairments in cerebellar disorders.